How Generalizable Are Randomized Controlled Trials (RCTs) in Staphylococcus aureus Bacteremia? A Description of the Mortality Gap Between RCTs and Observational Studies . (4th March 2022) - Bai, Anthony D; Lo, Carson K L; Komorowski, Adam S; Suresh, Mallika; Guo, Kevin; Garg, Akhil; Tandon, Pranav; Senecal, Julien; Del Corpo, Olivier; Stefanova, Isabella; Fogarty, Clare; Butler-Laporte, Guillaume; et al.
Abstract: In Staphylococcus aureus bacteremia, mortality rates in randomized controlled trials (RCTs) are consistently lower than observational studies. Stringent eligibility criteria and omission of early deaths in RCTs contribute to this mortality gap. Clinicians should acknowledge the possibility of a lower treatment effect when applying RCT results to bedside care.